Long term calibration of the Noble gas temperature system in a shallow unconfined Pleistocene aquifer - Hall, C. M.; Castro, M. C.; Lohmann, K. C.; Ma, L. (Eos Trans. AGU Fall Meeting Supplement, 2005)
id: 438

Noble gases and stable isotopes in a shallow aquifer in southern Michigan: Implications for noble gas paleotemperature reconstructions for cool climates - Hall, C. M.; Castro, M. C.; Lohmann, K. C.; Ma, L. (Geophysical Research Letters, 2005)
Noble gas data from the Glacial Drift, the shallowest aquifer in southern Michigan confirm findings by Ma et al. (2004) that modern noble gas temperatures (NGTs) are systematically below the current mean annual air temperature (MAAT) which, in turn, is similar to the ground temperature of these recharge waters. By tracking noble gas concentrations as well as stable isotope ratios through an autumn, winter, spring and into summer, we show that although water in this aquifer is modern, noble gases do not track the atmosphere on a short time scale. Specifically, excess He-3 and He-4 indicate that the gas environment at the water table is integrating conditions over years or decades rather than weeks or months. Our results are interpreted using various NGT interpretational models and possible mechanisms for the production of low apparent NGTs are discussed.
968qnTimes Cited:26 Cited References Count:14
Keywords: water